Impact of spectral quality of visible and UV light on the nutritional and the health-promoting qualities of leafy-vegetables and tomato - Lee, Myungjin (Kansas State University, 2020)
Spectral quality of radiation has a major impact on the growth, development, and nutritional quality of crops. The solar radiation spectrum reaching the earth consists of both visible and UV regions, which have significant effects on plant growth and a myriad of plant functions. The main objective of this study was to examine the role of spectral quality of supplemental light (visible and UV) on the nutritional quality of lettuce and tomato with regard to their health-promoting phytochemicals and essential nutrients. The study included two lettuce varieties, (Lactuca sativa L. cv. red leaf ‘New Red Fire’ and green leaf ‘Two Star’) and tomato (Solanum lycopersicum L. cv. ‘BHN-589’) grown under growth chamber, greenhouse, and field conditions. The effect of supplemental visible radiation (blue, red, or far-red) on lettuce was determined under supplemental lighting provided by light emitting diodes (LEDs) in growth chambers with a background of white light (fluorescent lighting-PAR 270 μmol/m²/s). Supplemental far-red produced higher biomass and larger leaf area in both lettuce varieties compared to the control plants. However, it had an inhibitory effect on the accumulation of many phenolic compounds in red leaf lettuce. On the one hand, in red lettuce, supplemental red radiation increased the accumulation of a number of phenolic compounds, while, on the other hand, supplemental blue radiation increased the accumulation of many phenolic compounds in green leaf lettuce. Thus, the results show that supplemental visible spectra of light can have a significant impact in enhancing the accumulation of health-promoting phytochemicals in lettuce. To determine the effect of supplemental UV on the nutritional quality in lettuce and tomato, the plants were grown under supplemental UV-A, UV-B, and UV-AB radiation using fluorescent lamps in a greenhouse. The overall response to these treatments was variable and was species and variety specific. UV-A produced a strong response in red leaf lettuce in improving the accumulation of many flavonoids. Higher accumulation of essential nutrients, including protein, phosphorus, calcium, magnesium, copper, zinc, and others, occurred in the green leaf lettuce in response to UV treatments. Supplemental UV-treatments of tomato plants, especially UV-B and UV-AB, produced higher accumulation of many phenolic compounds in mature fruits with no significant improvement in the essential nutrients. To further confirm the role of UV in enhancing the nutritional value of these crops, a field study was conducted where lettuce and tomato crops were grown in high tunnels covered with photo-selective poly covers to block solar UV radiation. Red leaf lettuce was the most responsive to the UV containing treatment with regard to the accumulation of phenolic compounds. Clear poly and exposing the crop to full sun 2 weeks prior to harvest produced the largest increase in many flavonoids. Overall, the results suggest that the spectral quality of light, especially having the full spectrum of UV, plays a significant role in the accumulation phenolic compounds and essential nutrients and in improving the health-promoting qualities of both lettuce and tomato.
Keywords: Spectral quality of visible and UV light; Nutritional and health-promoting qualities; Leafy-vegetables and tomato